VIDEO KARTUN DAN ANIMASI DAPAT MENURUNKAN TINGKAT KECEMASAN PRE OPERASI ANAK USIA PRA SEKOLAH - Ajeng Dwi Retnani, Titin Sutini, Suhendar Sulaeman (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2020)
Surgery requires a preoperative nursing action which is the initial stage of operative nursing, which starts from the time the patient is admitted into the patient's reception room and ends when the patient is transferred to the operating table for surgery. Psychological and physiological reactions to surgical procedures and anesthetic processes that allow for an anxiety response, especially in pre-school-aged children. Preschoolers who are sick and have to be hospitalized can experience unpleasant experiences and cause anxiety. They tend to refuse treatment and treatment that is being undertaken, causing delays to some actions including surgery. The purpose of this study was to analyze the effect of cartoon videos on reducing preoperative anxiety levels in pre-school age children. This research method uses quasi-experimental with a pre and post-test approach with out control. The sampling technique used purposive sampling with a sample of 20 children who were divided into 2 groups. This research instrument uses the HARS anxiety questionnaire. Data analysis using paired t-test. The results showed that the decrease in preoperative anxiety levels in pre-school children after being given a cartoon video intervention by 4.20, after being given an animated video intervention by 4.70. The results of the study also obtained p value> 0,000, which means the influence of cartoon videos and animated videos on reducing preoperative anxiety levels in pre-school age children. Suggestions that researchers can give are nurses can provide animation video interventions to minimize preoperative anxiety in pre-school age children.